Correlation between the perceived use and usefulness of grammar learning strategies among ESL undergraduate students - Mohamad, Faizah; Abdul Halim, Nur Syuhada; Md Johar, Elia; Abdul Kadir, Zaemah (Universiti Teknologi MARA, Kedah, 2025)
It has been a challenge for students to learn grammar as it is complex and difficult for students to understand. Students have to employ strategies that could assist them to master the grammatical items learnt. The present research investigated the perceived use and usefulness of grammar learning strategies among ESL undergraduate students in one public university in Malaysia. It also examined the perceived use and perceived usefulness of grammar learning strategies based on students’ proficiency levels. The study employed quantitative research using a set of questionnaires which was randomly distributed via google forms to students who took a grammar course, and 75 students responded to the questionnaire. The data gathered were analyzed using both descriptive and inferential statistics. The findings indicated that there were significant correlations between the perceived use and usefulness for all grammar learning strategies. The findings also revealed that social strategies were most used and perceived as useful in learning grammar by students with all levels of proficiency. There were significant mean differences in the perceived use, but no significant differences found in the perceived usefulness in grammar learning strategies based on students’ proficiency levels. Since students with high proficiency level use all grammar learning strategies more than less proficient students, they could guide their friends in learning grammar. Students with different levels of language proficiency seem to perceive the usefulness of their grammar learning strategies equally. Therefore, teachers can use a diverse range of resources and activities in their classrooms without putting any students at a disadvantage.